2019
DOI: 10.1017/s0266467419000245
|View full text |Cite
|
Sign up to set email alerts
|

Extrafloral nectar as a driver of ant community spatial structure along disturbance and rainfall gradients in Brazilian dry forest

Abstract: Although extrafloral nectar (EFN) is a key food resource for arboreal ants, its role in structuring ground-nesting ant communities has received little attention, despite these ants also being frequent EFN-attendants. We investigated the role of EFN as a driver of the spatial structure of ground-nesting ant communities occurring in dry forest in north-eastern Brazil. We examined the effects on this relationship of two global drivers of biodiversity decline, chronic anthropogenic disturbance and climate change (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Indeed, L. neotropicum is known to visit EFN of I. edulis in agroecosystems (Sinisterra et al, 2016) and perhaps the same can occur with S. invicta. Ant species that are frequent users of EFN are known to nest closer to EFN-producing plants (Silva et al, 2019). Pachycondyla harpax usually nests underground in the vicinity of trees (Grüter et al, 2018), and although workers forage primarily on the ground, they can also be found on trees (Rocha et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, L. neotropicum is known to visit EFN of I. edulis in agroecosystems (Sinisterra et al, 2016) and perhaps the same can occur with S. invicta. Ant species that are frequent users of EFN are known to nest closer to EFN-producing plants (Silva et al, 2019). Pachycondyla harpax usually nests underground in the vicinity of trees (Grüter et al, 2018), and although workers forage primarily on the ground, they can also be found on trees (Rocha et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between the environment and mutualistic ant-partners is a main factor controlling the outcomes in ant-plant interactions (Nogueira et al 2015, Bächtold et al 2016. Most of what we know about the spatiotemporal variation in ant-plant relationships comes from studies in natural areas; however, EFN plants also occur in fragments within urban settings, such as parks (Clarke et al 2008, Silva et al 2019. In a broad sense, urban parks are considered isolated forest habitats surrounded by an urban matrix without terrestrial connections/corridors with natural areas and are susceptible to anthropogenic disturbances (Pacheco & Vasconcelos 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dominant ant species are likely to monopolize the most attractive plant species in the community, displacing subordinate species to less attractive plants (Blüthgen and Fiedler 2004c). At a broad scale, this kind of assortative pairing can predictably shape the patterns of ant-plant interaction along spatial gradients (Dáttilo et al 2013b), especially along those in which the competitive pressure among ant species is also variable (Leal and Peixoto 2017, da Silva et al 2019, Lasmar et al 2021. In this case, ant-plant interactions should become less generalized and form groups of interacting species as the stronger competitive pressure among ant species, with dominant and subordinate ants interacting with a more dissimilar group of plants in the community.…”
Section: Introductionmentioning
confidence: 99%